Controle de erosão em estradas rurais não pavimentadas, utilizando sistema de terraceamento com gradiente associado a bacias de captação - Casarin, Rui Donizete [UNESP]; de Oliveira, Eduardo Luiz [UNESP] (My University, 2009)
The agricultural unpaved roads are important road structures for the economic and social agricultural development of the Nation, and the erosion provoked by rain water in the road bed and sides are closely related to bad draining, one of the main factors for their degradation. In order to make the draining system adequate, it is necessary to know about erodibility, infiltration capacity of water in the ground and adoption of mechanical slope abatement with grid elevation and water interception. This study presents drainage model through the construction of terraces with gradient transversally associated to the capitation basin in abruptic red dystrophic argisol soils, medium sandy texture, based on slops abatement techniques, elevating the road bed and deviating flow. The grain sized fractions of this ground (sand, silt, clay) and the aggregate stability indicated that this ground, under anthropic action, presents erosive processes resulting in superficial draining with ground hauling, sanding sources and courses of water situation below roads, providing great environmental impacts in the hydric bodies. The reduction of erosion problems in these unpaved roads is in the adoption of measures that intercept waters from the draining of their stream bed itself, as well as pluvial waters comings from adjacent areas of contribution, that are collected and conducted to inlaid terraces and capitation basis.
Control of erosion in ruralunpaved roads utilizing a terrace system with gradient associated to capitation basin
Keywords: Erosion in agricultural roads; Mechanical soil conservation practices; Pluvial water containment; Water infiltration in the soil; agricultural land; basin; environmental impact; erodibility; grain size; infiltration; road; soil conservation; soil degradation; soil erosion; streamwater; terrace